Studi Pendahuluan tentang Dampak Penerapan Model Pembelajaran CCTT terhadap Aktivitas Belajar Biologi: Preliminary Study on The Impact of Application of CCTT Learning Model on Biology Learning Activities - Rahmat Hidayat; Yeliza Frienti (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
The aplication of learning of biology often deviates from the planning. The problem that comes is low students activities in learning, because not all students participate in learning. The couple card teams tournament (CCTT) learning model was developed to solve these problems, so that each student was actively involved in learning. The objective of this study is to describe the impact of the application of CCTT learning model on learning activities of students Class XII IPA 2 SMA Negeri 1 Merlung Tanjung Jabung Barat. This study was a descriptive research, the subjects were the 30 of class XII IPA 2 school year 2018/2019. Research data were collected through observation and documentation methods. The data were analyzed qualitatively through reduction and display of data, and make conclusions. The results showed that CCTT learning model was successfully applied in Class XII IPA 2, which is seen from the average of scores in answering other groups questions by 5,50, which means that each group answered 6 correct answers in each round. The application of this learning model has triggered biology learning activities of students, which can be seen that 25 students involved in learning, with average achievement of sub-indicators of learning activities up to 83.33% in the very active category. The results confirmed that CCTT learning model has a good impact on learning activities and was appropriate applied to triggered students learning activities in subject of biology. Keywoards: CCTT Learning Model, Learning Activities, Biology Abstrak : Pembelajaran biologi dalam penerapannya kerap tidak sesuai dengan perencanaan. Masalah yang muncul ialah aktivitas siswa yang rendah karena tidak semua siswa ikut serta dalam pembelajaran. Model pembelajaran couple card teams tournament (CCTT) dikembangan untuk menyelesaikan masalah tersebut, sehingga setiap siswa terlibat secara aktif dalam pembelajaran. Tujuan penelitian ini ialah untuk mengetahui dampak penerapan model pembelajaran CCTT terhadap aktivitas belajar siswa kelas XII IPA 2 SMA Negeri 1 Merlung Tanjung Jabung Barat. Penelitian ini adalah penelitian deskriptif dengan jumlah subjek penelitian sebanyak 30 orang siswa kelas XII IPA 2 tahun pelajaran 2018/2019. Data penelitian dikumpulkan melalui metode pengamatan dan dokumentasi. Data dianalisis secara kualitatif melalui tahapan reduksi data, sajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa model pembelajaran CCTT berhasil diterapkan di kelas XII IPA 2, yang terlihat dari rata-rata capaian nilai siswa dalam menjawab pertanyan kelompok lain sebesar 5,50 yang artinya rata-rata setiap kelompok menjawab 6 jawaban benar dalam setiap putaran. Penerapan model pembelajaran CCTT dapat memicu aktivitas belajar siswa kelas XII IPA 2 pada mata pelajaran biologi, yang terlihat dari rata-rata 25 siswa terlibat dalam aktivitas pembelajaran, dengan rata-rata capaian sub-indikator aktivitas belajar hingga 83,33% dalam kategori sangat aktif. Hasil tersebut menegaskan bahwa model pembelajaran CCTT sangat baik diterapkan untuk memicu aktivitas belajar siswa pada mata pelajaran biologi. Kata kunci: model pembelajaran CCTT, aktivitas belajar, pembelajaran biologi